Entrepreneurial Knowledge and Perceptions of Entrepreneurship on Entrepreneurial Interest with Support for Self-Efficacy as a Mediating Variable in Sukabumi City Students - Intan Kamil Dwi Permadi; R. Deni Muhammad Danial; Asep Muhamad Ramdan (Dinasti Publisher, 2025)
This study aims to analyze the effect of entrepreneurial knowledge and entrepreneurial perceptions on entrepreneurial interest with self-efficacy as a mediating variable in final year undergraduate students in Sukabumi City. Quantitative approach was used with survey method through questionnaires to 180 students from various universities. Data analysis was conducted using Structural Equation Modeling (SEM) with the help of SmartPLS 4 software. The results showed that entrepreneurial knowledge and entrepreneurial perceptions have a positive and significant effect on entrepreneurial interest. Self-efficacy also proved to play a significant mediating role in strengthening the relationship between the independent variables and entrepreneurial interest. This finding confirms the importance of increasing knowledge capacity and positive perceptions of entrepreneurship, supported by self-efficacy in encouraging students' intention to become entrepreneurs. This research provides practical implications for higher education institutions in designing entrepreneurship programs that are able to foster entrepreneurial interest from an early age.